Determining Factors of Financial Distress in Retail Companies (Listed on Indonesia Stock Exchange 2016-2020) - Supriadi, Ade; Diadeci, Anin; Dwisatria, Muhammad Rafli; Zahra, Nada; Fauziah, Sarah; Fathonah, Andina Nur (CENTRAL ASIA AND THE CAUCASUS, 2022)
The retail sector has a great role to the national economy, where the retail sector is able to absorb a large workforce and contribute greatly to national economic growth. This study aims to discover the factors that affect financial distress in retail subsector (retail trading) listed on Indonesia Stock Exchange. This study is a qualitative with secondary data sources obtained from the official website of each company and from the Indonesia Stock Exchange while the method for sampling determination is purposive sampling with a population of 20 companies during 2016-2020. Statistical methods used to answer the formulation of the problem using logistic regression. Financial ratios, sales growth and cash flow operating activities are used as proxy in predicting distress condition. It is proposed the formulation of the problem to discover the factors that affect financial distress. From the result of data collected and tested showed that variable liquidity ratio, profitability ratio, activity ratio had an effect, while the leverage ratio, sales growth, and operational cash flow had no effect on financial distress